Agricultural Economy and Welfare Outcomes: Evidence from Central Kalimantan Province, Indonesia - Arniwaty, Arniwaty (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2026)
This study examines the impact of the agricultural sector’s contribution on poverty levels in Central Kalimantan Province, Indonesia. Using a quantitative approach, the analysis employs balanced panel data covering districts and municipalities over the 2019–2023 period. Poverty rate is used as the dependent variable, while the agricultural sector’s share of gross regional domestic product (GRDP), GRDP per capita, and open unemployment rate are included as explanatory variables. Panel data regression techniques are applied, with model selection conducted through Chow and Hausman tests. The results indicate that the Fixed Effect Model is the most appropriate specification. Empirical findings show that the agricultural sector’s contribution has a negative and statistically significant effect on poverty, suggesting that increases in agricultural economic activity are associated with reductions in poverty levels. GRDP per capita also exhibits a significant negative relationship with poverty, while open unemployment has a positive and significant effect, indicating that labor market conditions play a crucial role in shaping welfare outcomes. These findings highlight that agriculture remains an important pathway for poverty reduction in resource-based regions, particularly when supported by employment creation and income growth. The study contributes to the regional development literature by providing district-level empirical evidence from a resource-rich province and offers policy-relevant insights for designing inclusive poverty reduction strategies